Good outcomes of elbow arthroscopy-assisted absorbable screw fixation for capitellum fracture of the humerus in children: a case series - You, Chao; Cheng, Zhen; Xia, Yongjie; Deng, Chao; Zhou, Yibiao; Sun, Yiyuan; Fu, Guibing (Frontiers in Pediatrics, 2023)
Background:Capitellum fractures are rare coronal fractures of the distal humerus which accounts for 6% of all distal humeral fractures and only 1% of all elbow fractures. The purpose of this study was to investigate the efficacy and complications of arthroscopically assisted reduction and fixation with absorbable screws for capitellar fracture of the humerus in children. Methods:This was a retrospective case series study, which considered four patients (4 elbows), ranging from 10 to 15 years old, who were treated by arthroscopic-assisted percutaneous absorbable screw between 2018 and 2020. The elbow flexion-extension and forearm supination-pronation ranges of motion (ROM) were measured at the preoperative examination and last follow-up examination. Finally, the clinical and radiological results were assessed. Results:The result of operations is satisfactory. The mean follow-up was 3.0 years (range 2–3.8 years). Average range of motion significantly improved from pre- to postoperation, with forearm supination from 60°(50°-60°) to 90°(90°) and pronation improved from 75°(70°-80°) to 90°(90°). The postoperative elbow flexion-extension range of motion was significantly higher compared with range of motion before surgery (P＜0.001; r=0.949). At the final follow-up examination, the Mayo Elbow Performance Score was excellent. Satisfactory clinical results were achieved in all patients, and no postoperative complications were observed. Conclusions:It is an effective and safe surgical option to use arthroscopic-assisted percutaneous absorbable screw fixation for treating capitellum fracture of the humerus without any complications in children. Level of evidence:Level IV; Case Series